Effect of Nanochitosan Gel With 1% Amethyst Seed Extract on IL-10 Expression - Aquarina Hapsari; Indra Bramanti; Iwa Sutardjo RS (Scientific Dental Journal, 2024)
Background: Amethyst (Datura metel L) is Indonesia's natural plant resources which is used by wide community as an anti-inflammatory agent. Nanochitosan technology is developed in topical gel preparation to overcome weaknesses of bioavailability, solubility, absorption active compound, and low ability to reach target cell. Objectives: This research aims to determine effect 1% nanochitosan amethyst seed extract  (ASE) gel of IL-10 expression in the inflammatory phase of wound healing process Rattus norvegicus. Methods: 1% nanochitosan ASE gel was obtained via gelation-ionic chitosan-NaTPP method. The research subjects consist of 30 Rattus norvegicus which were divided into 4 groups, i.e positive control (Benzydamine-HCl), negative control, and 2 treatment groups (1%  chitosan ASE gel and 1% nanochitosan ASE gel). Each gel applied twice a day in the morning and evening. The inflammatory model had 3 rats per group. All rats were injured using punch biopsy on mandibular labial gingiva and applied to gel treatment. Decapitation was carried out according to group, i.e 0,1st,3rd,and 5th days. Histological preparations were made using immunohistochemical staining to observe IL-10 expression. Data were analyzed using Kruskal Wallis test with 95% confidence level. Results: Kruskal Wallis test showed that IL-10 expression on 0,1st,3rd, and 5th days of the 1%  nanochitosan ASE gel and 1% chitosan ASE gel groups had increased, and there was a significant difference between the negative control group (0 day) and treatment group on 1st day (p<0.05). Tukey test results showed there was no significant difference between increase in 1% nanochitosan ASE gel group and the 1% chitosan ASE gel group (p>0.05). Conclusion: 1%  nanochitosan ASE gel has the same effect as 1% chitosan ASE gel on increasing IL-10 expression in inflammatory phase of gingival wound healing Rattus norvegicus. Keywords: amethyst seeds, anti-inflammatory, gingiva, nanochitosan, IL-10 , Rattus norvegicus